Confucian Philosophy on Cultivating Effective Leadership and Personality – An Exploration - S. Mohan Raj, Dr V.Sunitha (International Journal of Advanced Science and Technology, 2020)
Confucius the Chinese philosopher propounds valuable ideals. The major surviving Confucian source is the text Lun Yu: The Analects presents the teachings of Confucius. Confucius views an individual as an interconnected structure of society. An individual has to follow good virtues, harmony, trust, an maintain social relationships. Moral traits can build good leadership and followership. These qualities are essential in business and organisation sector. The present study discusses the Confucian philosophy of personality and leadership. The cardinal virtues of the Confucian thoughts had a strong influence on culture of China and society. The concepts of recent leadership traits are akin to the Confucian ideals.Confucian leadership thoughts prompt an individual to frame as an ideal human and ideal leader.